Emergence of an Entrepreneurial Economy in an Uncertain Environment: the case of China - Trigo, V.; Qin Lang (Global Clusters of Innovation: Entrepreneurial engines of economic growth around the world, 2014)
Private enterprises have played a vital role in promoting China’s entrepreneurial economy in an environment that has favoured gradualism and experimentation. This chapter reviews their development history since reform and opening in late 1978 and examines the many hurdles they had to overcome in order to become a major contributor to the country’s economic growth as well as their current status. The role of the individual entrepreneur is emphasised through the many examples and real life stories in the chapter that highlight his/her skill and resilience in dealing not only with market risks and barriers but also with the volatility of policies and financing difficulties that are overcome through the continuous weaving of social capital and social networks. The chapter provides further insights into our understanding on the process of China’s introduction of market principles that have been a product of persistent pushes from the bottom and gradual authorisation from the top.